Possible ways of improving the health management system of male staff at atomic industry enterprises - D. Ye. Kalinkin; A. B. Karpov; R. M. Takhauov; S. M. Khlynin; Yu. A. Samoilova; I. V. Shiryayeva; D. B. Bul’dovich (Бюллетень сибирской медицины, 2012)
Oncological morbidity among the male workers of the Siberian Group of Chemical Enterprises (SGCE) in 1970—2005 was studied. Increased related risk (in comparison with the standard) of malignant neoplasms of resiratory and digestive tract, urinary ways and genitals was found. On the basis of the received results proposals on perfection of system of health protection of the man's personnel of the enterprises of nuclear branch are made.